The effect of unadsorbed proteins on the physiochemical properties of the heteroaggregates of oppositely charged lactoferrin coated lutein droplets and whey protein isolate coated DHA droplets. Issue 7 (5th July 2018) - Li, Xin; Wang, Xu; Liu, Jiawei; Xu, Duoxia; Cao, Yanping; Sun, Baoguo
Abstract : It was reported that the controlled heteroaggregation of oppositely charged lactoferrin (LF)-lutein droplets and whey protein isolate (WPI)-DHA droplets enhanced the physicochemical properties of emulsions. Abstract : It was reported that the controlled heteroaggregation of oppositely charged lactoferrin (LF)-lutein droplets and whey protein isolate (WPI)-DHA droplets enhanced the physicochemical properties of emulsions. The effect of the unadsorbed proteins on the physicochemical properties of the heteroaggregates of emulsions has not been clear. Therefore, the effects of unadsorbed proteins on the physicochemical stability of heteroaggregates of LF-lutein droplets and WPI-DHA droplets were investigated. The particle size, zeta-potential, transmission-physical stability, microstructure were observed by confocal laser scanning microscopy (CLSM) and cryo-scanning electron microscopy (cryo-SEM) and the chemical stability (lutein degradation and DHA oxidation) of the unwashed and washed heteroaggregates were measured. The results showed that compared with unwashed emulsions, the particle sizes and instability indexes of WPI-DHA emulsions, heteroaggregated LF-lutein/WPI-DHA emulsions and LF-lutein emulsions changed after washing. The instability index of washed-1 heteroaggregated LF-lutein/WPI-DHA emulsion was 10.5 times greater compared with the unwashed samples. The microstructure images showed that the washed single and heteroaggregated emulsions resulted in creaming. The unadsorbed proteins had a great protective effect on the physical stability of the emulsions, especially for the heteroaggregated LF-lutein/WPI-DHA emulsion. The degradation rate of lutein, lipid hydroperoxides and thiobarbituric acid reactive substance (TBARS) values of DHA in washed single and heteroaggregated emulsions were higher than those of the unwashed samples. This proved that the unadsorbed proteins dominated the physicochemical stabilities of heteroaggregates. This laid the foundation for the study of a delivery system of functional component heteroaggregates.